The needs, preferences, and experiences of LGBT + people living with dementia: a systematic review with thematic synthesis - Claude Chidiac; Catherine Walshe; Jane Lowers; Nancy Preston (BMC Geriatrics)
Abstract Background LGBT + people are disproportionately at an increased risk for developing dementia. Dementia can compound the impact of stigma and social marginalisation experienced by LGBT + people, and is likely to create barriers to accessing healthcare services. Understanding the needs, preferences, and experiences of LGBT + people with dementia will help support high quality individualised care. The aim of this review is to explore and synthesise the evidence on the needs, preferences, and experiences of LGBT + people with dementia. Methods Systematic review with thematic synthesis. The search strategy combined concepts of gender and sexual minorities, and dementia. MEDLINE Complete, PsycInfo, CINAHL, and Academic Search Ultimate were searched until March 2024. Relevant published papers in the English language were included, regardless of design or type. Data were analysed using thematic analysis. Findings were discussed from a queer lens. Results Out of 1537 initial titles, 16 papers were included. Majority were published in the UK (n = 8), followed by USA (n = 4), Canada (n = 2), and Australia (n = 2). Of 16 papers, two were empirical qualitative studies, one used a subset of qualitative data from a previous study alongside other sources (literature review, reflection, policy) for data analysis, and 13 papers were non-empirical. The experiences primarily focused on actual or anticipated discrimination, and how the lifetime experiences of oppression, trauma, and other stressors can impact on the experience of dementia. Many of the needs captured focused on safety and control in identity disclosure and expression, and access to love, intimacy, and social networks. In addition, maintaining personhood through institutional safety, psychological safety, and attachment through relationships and couplehood were highlighted. Data on preferences were not explicit. Conclusion The robustness of the science is weak regarding the needs, preferences, and experiences of LGBT + people with dementia. Designing and implementing dementia-related policies through a queer intersectional lens, along with embedded cultural safety education programmes, are needed. Further research that includes the voice of LGBT + people with dementia coupled with healthcare professionals’ perspective is needed.